Pengembangan Mental Health Dalam Perspektif Konseling Pendidikan Islam Di Sekolah Dasar Islam - Hadini Hadini; M. Imamuddin; Masbur Masbur; Lukman Hakim; Zaharuddin M. (Institut Agama Islam Hidayatullah Batam, 2025)
Mental health condition must be developed. In this study, the library research method was used. The researcher identified literature in the form of journals, both national and international, book sources, research results related to the topic being studied, namely examining general theories as a basis for the mental health development model in Islamic Educational Counseling. In the literature study, various studies that have been conducted by previous researchers regarding the topic to be studied were also traced. From the results of the study, the form of mental health development in Islamic Educational Counseling was found. First, There are several perspectives put forward by various Counseling experts regarding mental health. Alder, Carl Gustav Jung, Abraham Maslow, and Carl Rogers focused. Second, in the view of Islamic Educational Counseling, mental health is a form of mental health or a healthy soul that is manifested in the form of the desire for al muthmainnah. Third, in developing human mental health, the tahalli aspect is the main aspect that must be developed by Islamic Educational Counseling, namely by optimizing human character through the actualization of the values of the Asma'ul Husana.